2008
DOI: 10.1002/ptr.2665
|View full text |Cite
|
Sign up to set email alerts
|

trans‐resveratrol alone and hydroxystilbenes of rhubarb (Rheum rhaponticum L.) root reduce liver damage induced by chronic ethanol administration: a comparative study in mice

Abstract: The hepatoprotective effects and pharmacokinetics of trans-resveratrol and hydroxystilbenes of the garden rhubarb (Rheum rhaponticum L., R. rhaponticum) root ethanol extract were studied. Ethanol was administered to male BALB/c mice for 35 days in an inhalation chamber. During this time vehicle, trans-resveratrol (20 mg/kg per day) or R. rhaponticum extract was intraperitoneally (i.p.) administered and mice were sacrificed for the collection of liver and blood. In an additional experiment, the level of parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 44 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…A review documents evidence for the favorable effect entailing destruction of cancer-initiating ROS by AO action (see Introduction). Liver damage caused by chronic alcohol consumption was reduced by RVT 223. Inhibition of oxidation of polyunsaturated fatty acids is proposed as a basis of the hepatoprotective effect.…”
Section: Livermentioning
confidence: 99%
“…A review documents evidence for the favorable effect entailing destruction of cancer-initiating ROS by AO action (see Introduction). Liver damage caused by chronic alcohol consumption was reduced by RVT 223. Inhibition of oxidation of polyunsaturated fatty acids is proposed as a basis of the hepatoprotective effect.…”
Section: Livermentioning
confidence: 99%
“…As one of the most famous medicinal herbs, rhubarb (Radix et Rhizome Rhei) is widely used in oriental medicine in Asian countries, and it is also an ingredient in numerous medicinal remedies of the ancient Greeks and Romans. Many recent studies have also revealed that rhubarb has antibacterial (Wang et al, 2010), anticancer (Shia et al, 2011a), anti-inflammation (Moon et al, 2006) and life-protecting effects (Raal et al, 2009). In addition, recent clinical trials demonstrated that rhubarb could significantly improve the endothelial function of the brachial artery (Liu et al, 2007) and ameliorate intestinal permeability (Fang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…With its antioxidant and anti‐inflammatory effects, there have been numerous studies on the prevention and treatment of hepatotoxicity due to various drugs and toxins about resveratrol. It has been shown to exhibit protective properties in hepatotoxicity developing in association with various agents, such as paracetamol, carbon tetrachloride (CCl 4 ) and alcohol . In addition to the preclinical in vitro and in vivo studies, recent studies including systematic reviews have demonstrated that resveratrol provides liver protection against cholestatic, drug‐ and alcohol‐induced injury.…”
Section: Objectivementioning
confidence: 99%